Factor (5a-3)^2-6(5a-3)+9

Math
(5a-3)2-6(5a-3)+9
Let u=5a-3. Substitute u for all occurrences of 5a-3.
u2-6u+9
Factor using the perfect square rule.
Tap for more steps…
Rewrite 9 as 32.
u2-6u+32
Check the middle term by multiplying 2ab and compare this result with the middle term in the original expression.
2ab=2⋅u⋅-3
Simplify.
2ab=-6u
Factor using the perfect square trinomial rule a2-2ab+b2=(a-b)2, where a=u and b=-3.
(u-3)2
(u-3)2
Replace all occurrences of u with 5a-3.
(5a-3-3)2
Subtract 3 from -3.
(5a-6)2
Factor (5a-3)^2-6(5a-3)+9

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top